THE IMPORTANCE OF ASSESSING ETHICAL AND MORAL STANDARDS IN THE MEDIA SPACE - Kamoliddin Turayev Samadovich (American Journals Publishing, 2025)
This article examines the transition from reality to virtuality in human relations, which has led to the acceleration of processes. Universal human and moral values that are dear to humans have gradually lost their essence under the influence of digital technologies. The article presents ideas on how, in the era of media use and information literacy, to maintain moral standards that are important for humans in the world, so as not to forget their essence and preserve their human image.
Keywords: Media, virtual network, strategy, system, gradation, information literacy, moral standards, universal human and ethical values.